Formação permanente em educação especial: aproximações e afastamentos na/da docência inclusiva - Carvalho, Luciana Carrion (2020)
This study results from the PhD research in Education, linked to the Research Line - LP1 “Teaching, Knowledge and Professional Development” of the Graduate Program in Education at the Federal University of Santa Maria - PPGE / UFSM, and GEPFICA - Grupo de Estudos e Pesquisa sobre Formação Inicial, Continuada e Alfabetização. The study addresses the permanent training of teachers in Special Education at the Instituto Federal Catarinense, from the perspective of Inclusive Education. The research explores the training processes and how they influence the decision making and, consequently, their epistemological positions conduct in the Rectory and inside their campuses. The investigation consists in “consciousness” as an important movement for transformation, according to Freire (2016), dealing with unveiling and awareness, not as synonyms of consciousness, but as participants in the process for the critical awareness development of consciousness, therefore, awareness for the self (trans)formation. We pursue to understand it as a device for the permanent training of teachers, using qualitative research, in a critical-dialectic approach, through the methodology of Investigative-Formative Dialogic Circles. In this sense, inclusive teaching implies to all and all teachers, at all levels and educational modalities: the ethical, social, educational commitment, among others, to go beyond information about disability and its implications, but the search to understand the relationships between biological, social and educational factors related to learning processes (as well as teaching). In a reflexive, collaborative and supportive way we can understand that isolated actions with proposals of sporadic works do not break the barriers in the educational field. Therefore, Special Education teachers should act on the permanent training of teachers in institutional systemic work. In this direction, the research findings aim to promote spaces for critical reflection by the faculty on the inclusive education paradigm, rethinking concepts formerly thought and/or experienced. As theoretical support, we used studies by Antunes (2001, 2005), Beyer (2005), Bogdan; Bicklen (1994), Bourdieu (2011), Charlot (2000), Cunha (1989), Dufor (2005), Fernandes (1966), Freire (1998, 2013, 2016), Henz (2014, 2015), Henz; Freitas; Silveira (2018), Imbernón (2009), Januzzi (2012), Larrosa (2002), Mazzotta (1996), Mores (2005), Nogueira (1996), Nóvoa (1992), Passeggi; Abrahão; Delory-Momberger (2012), Sassaki (1999), Serres (2001), Toniolo; Henz (2018),, among others, as a subsidy for reflection and proposition for a new teaching, the “inclusive teaching”, designed for EBTT, Federal and Higher Education Institutes realities.